Factors Affecting Expression Level of Recombinant Human Epidermal Growth Factor in Escherichia coli BL21(DE3) and Size Exclusion Purification Thereof - Pratiwi, Riyona Desvy; Agustina, Nabella; Aminah, Aminah; Fuad, Asrul Muhamad (Annales Bogorienses, 2021)
Recombinant human epidermal growth factor (rhEGF) has been developed to provide the protein for therapeutic uses. Isopropyl β-d-1-thiogalactopyranoside (IPTG)-induced expression in Escherichia coli BL21(DE3) has shown the most effective system among other inducers systems in a similar host. However, suitable conditions related to IPTG concentration, incubation time, and incubation temperature are different depending on the amino acid content of the recombinant protein. This study aimed to evaluate the effects of various IPTG concentration, incubation time, and incubation temperature on rhEGF concentration. According to each analysis of those factors, induction with 0.05 mM IPTG for 2 h at 23°C was the most appropriate condition to obtain the highest concentration of rhEGF. The rhEGF was positively confirmed with a monoclonal antihEGF antibody and purified in high purity reaching 95.2%, yet recovery was low (1.44%) due to loss in fractions containing endogenous proteins. Therefore, further studies related to type of matrix, column length, and sample concentration in applying size exclusion chromatography are requested for higher recovery